Manusia Berkemampuan (Homo Capax): Fondasi Antropologi Filosofis Etika Belarasa dalam Konteks Pemulihan Korban Kekerasan Seksual menjadi Penyintas: Capable Being (Homo Capax): An Antropological Foundation for An Ethics of Compassion in the Context of Helping Victims of Sexual Violence to Restore Their Existence - Tobing, David (STF Driyarkara - Diskursus, 2023)
As a traumatic event, sexual violence does not only take a physical and psychological toll on the victims, but also causes existential crisis. In this light, we cannot restore the wellbeing of victims of sexual violence without restoring their own capability to exist as human beings in wholeness. Based on that condition, this article attempts to answer two problems: (i) what kind of ethics do we need in order to help victims of sexual violence restore their own existence as whole human beings? and (ii) what kind of human conception is presupposedby that ethics? To that question, this article suggests that (1) we need an ethics of compassion in order to help victims of sexual violence to restore their own existence as whole human beings and (2) it presupposes a specific conception of human being as a capable being (homo capax) in Ricoeurian perspective. Abstrak Sebagai peristiwa traumatik, kekerasan seksual tidak hanya memberikan dampak fisik dan mental, namun juga eksistensial. Karena itu, pemulihan korban kekerasan seksual menjadi penyintas adalah juga pemulihan daya eksistensial dari yang bersangkutan. Bertolak dari kondisi itu, artikel ini mengajukan pertanyaan “(i) etika seperti apakah yang memungkinkan terjadi proses pemulihan korban kekerasan seksual menjadi penyintas dan (ii) konsepsi manusia seperti apakah yang menjadi pengandaian dalam etika itu?” Terhadap pertanyaan itu, penulis mengajukan tesis bahwa (1) etika belarasa merupakan pandangan etika yang dapat membantu proses pemulihan korban kekerasan seksual menjadi penyintas dan (2) etika belarasa mengandaikan konsepsi manusia berdaya (the capable being) dalam pemikiran Paul Ricoeur. Kata-kata kunci: kekerasan seksual, diri, emosi, etika belarasa, manusia berdaya